Tuning of Smart Multifunctional Polymer Coatings Made by Zwitterionic Phosphorylcholines. Issue 1 (1st December 2019) - Münch, Alexander S.; Adam, Stefan; Fritzsche, Tina; Uhlmann, Petra
Abstract: In the last years, the generation of multifunctional coatings has been moved into the focus of interface modifications to expand the spectrum of material applications and to introduce new smart properties. Herein a promising multifunctional and universally usable coating with simultaneous antifouling, easy‐to‐clean, and anti‐fog functionality is presented based on smart polymer films consisting of copolymers with 2‐methacryloyloxyethyl phosphorylcholine (MPC), realizing the function of the film and photoreactive 4‐benzophenyl methacrylate (BPO), which is responsible for stability and crosslinking. The easy‐to‐clean effect is demonstrated qualitatively and quantitatively by oil droplet detachment experiments. The antifouling behavior against different germs is investigated by cell adhesion experiments. Furthermore the anti‐fog performance is shown by breathing on the surfaces. To study the influence of the different amounts of copolymerized BPO, the grafted films are characterized by atomic force microscopy (AFM), infrared spectroscopy (ATR‐FTIR), as well as contact angle measurements. In situ spectroscopic ellipsometry is performed to investigate the swelling behavior of the thin films as a function of the time of UV‐irradiation. It is found that a degree of swelling of 15 and a water contact angle of less than 12° are the key parameters necessary for the generation of multifunctional coatings. Abstract : A multifunctional coating, combining easy‐to‐clean, anti‐fog, and antifouling properties is achieved by preparing thin films of a set of co‐polymers of 2‐methacryloyloxyethyl phosphorylcholine (MPC) and benzophenone (BPO) to study structure–property relationships. The study shows that an exactly balanced ratio between thickness of dry films, degree of swelling, and water contact angle is necessary to create surface coatings with tailored properties.